2014
DOI: 10.1021/nn502635y
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Holey Graphene Synthesis and Dense Electrode Fabrication toward High-Performance Ultracapacitors

Abstract: Graphene has attracted a lot of attention for ultracapacitor electrodes because of its high electrical conductivity, high surface area, and superb chemical stability. However, poor volumetric capacitive performance of typical graphene-based electrodes has hindered their practical applications because of the extremely low density. Herein we report a scalable synthesis method of holey graphene (h-Graphene) in a single step without using any catalysts or special chemicals. The film made of the as-synthesized h-Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
188
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 223 publications
(197 citation statements)
references
References 45 publications
8
188
1
Order By: Relevance
“…However, the GNCN//GNCN symmetric supercapacitor in 6 M KOH electrolyte delivers a low energy density of 7.2 Wh kg À 1 due to its low voltage window (1 V). More interestingly, the GNCN//GNCN symmetric supercapacitor also exhibits a high volumetric energy density of 26 Wh L À 1 in 1 M Na 2 SO 4 aqueous electrolyte, higher than most previously reported carbon based supercapacitors in aqueous electrolyte (Figure 4b) [60,63,[67][68][69][70].…”
Section: Resultsmentioning
confidence: 56%
“…However, the GNCN//GNCN symmetric supercapacitor in 6 M KOH electrolyte delivers a low energy density of 7.2 Wh kg À 1 due to its low voltage window (1 V). More interestingly, the GNCN//GNCN symmetric supercapacitor also exhibits a high volumetric energy density of 26 Wh L À 1 in 1 M Na 2 SO 4 aqueous electrolyte, higher than most previously reported carbon based supercapacitors in aqueous electrolyte (Figure 4b) [60,63,[67][68][69][70].…”
Section: Resultsmentioning
confidence: 56%
“…Our choice was also influenced by the number of techniques that enable the introduction of nanoscale pores of arbitrary size and location to graphene, including both electron-beam bombardment and chemical approaches. [30][31][32][33][34][35][36][37][38][39] These techniques will ultimately provide flexibility and precision in pattern shape and scale, including precise hole size and pitch.…”
mentioning
confidence: 99%
“…Introducing pores in graphene platelets may facilitate ion/solvent diffusion across the graphene layers, enabling the assembly more ion-accessible even when the layers are densely stacked. The difference between the thermal stabilities of the crystalline and the non-crystalline regions in thermally exfoliated graphite oxide (TEGO) has been exploited to create holes by carefully controlling the temperature of the annealing atomosphere [61]. It was found that such a holey-graphene is easier to disperse in N-methyl-2-pyrrolidone (NMP) when compared to the original TEGO, since the mesopores created during the processing facilitated the penetration of NMP molecules.…”
Section: Strategies To Improve the Volumetric Performance Of Electrodmentioning
confidence: 99%